Impacts of surface wear of attachments on maxillary canine distalization with clear aligners: a three-dimensional finite element study - Li, Qiuying; Xu, Bowen; Fang, Dongyu; Yang, Kai (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesThis study established three-dimensional finite element models to explore the impacts of surface wear of attachments on maxillary canine distalization with clear aligners, thereby guiding the clinical application of attachments and enhancing the efficiency of clear aligner therapy.Materials and methodsFinite element models of maxillary canine distalization, including the maxilla, dentition, periodontal ligament, attachments (in both initial and worn states), and clear aligners, were established. Two groups of attachments (vertical rectangular attachment and optimized root control attachment) and five working conditions representing different degrees of attachment wear (M0, M2, M4, M6, and M8) were designed for canine distalization. Tooth displacement and equivalent stress in the roots and periodontal ligaments were analyzed.ResultsThe canines in both groups exhibited a tipping movement pattern under all working conditions. By M8, the distal displacement of the canine crown, the equivalent stress values in the roots, and the equivalent stress values in the periodontal ligaments in the rectangular attachment group decreased by 12.04%, 30.80%, and 16.48%, respectively, compared to M0. In the optimized root control attachment group, these values decreased by 24.98%, 34.69%, and 19.15%, respectively. However, under all working conditions, the canines in the rectangular attachment group presented greater displacement and stress. The greatest reduction in canine crown distal displacement and stress values was observed between M6 and M8 in the rectangular attachment group, but the efficiency of canine distalization was still 64.30% at M8, with minimal change. In the optimized root control attachment group, the greatest reduction was observed in M4–M6, and the efficiency of canine distalization decreased to less than 60% in response to M6.ConclusionThe canines tended to tip when maxillary canine distalization was performed with clear aligners. Attachment wear led to a reduction in the efficiency of canine distalization. Compared with optimized root control attachments, the impact was less significant for rectangular attachments. Once optimized root control attachments have been in place for more than 4 months and maxillary canine distalization is still required, orthodontists should closely monitor the wear of these attachments. If necessary, timely restoration or rebonding of the attachments is recommended.